LOGIKA BERPIKIR: INTEGRASI TEORI KEBENARAN DAN TEKNOLOGI DETEKSI HOAKS - Rahma Vivianita; Dea Ayu Wulandari; Mahdum; Jimmy Copriady (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Technological advancements in the current digital era have triggered an information explosion that not only enriches access to knowledge but also creates increasingly complex epistemic challenges. This condition demands an integration of philosophical inquiry and technological use to strengthen society’s ability to assess the truthfulness of information. This study aims to develop a model of Philosophical Digital Literacy by synthesizing findings on logical thinking, truth theories, and hoax-detection technology. The research employs a systematic literature review following the PRISMA protocol, analyzing 10 selected articles, including four national and six international publications published between 2018 and 2025. The synthesis reveals three main findings: (1) practical logical thinking requires a strong foundation in truth theories; (2) hoax detection technology serves as cognitive augmentation in the information verification process; and (3) the integration of both leads to the concept of Philosophical Digital Literacy as a comprehensive approach. This study recommends the implementation of the Philosophical Digital Literacy model in digital literacy curricula, positioning truth theories as the core conceptual framework. Philosophical Digital Literacy offers a new paradigm that combines the depth of philosophical reflection with technological utility to build a more critical and wise Indonesian digital society.